Optimization of the biofilter in the domestic wastewater treatment system. (Retention time of the wastewater in the biofilter chamber) - Teh Nur Akmal, binti Kusni. (Universiti Malaysia Sarawak (UNIMAS), 2006)
The mai n purpose of this research was to determine the performance ofbiofilter in removing organic matter by optim izing the retention time of the wastewater in contact with the microorganisms. The wastewater used was domestic wastewater. In optimizing the retention time, the biofilter column adjusted at three ditTerent lengths which were 20cm, 40cm and 55cm under continuous spraying in 6 to 12 hours cycle in two replicates. The retention time of three different lengths was determined by using bromophenol as dye measuremen t. Result showed that, for 20cm length with 55s of retention time has 50.93% of BOD removal wh ile at 40cm length with 125s of retention time only 40.62% of BOD removal. The efficiency of BOD removal required 61.07% for 55cm bed length with 145s of retention time.